Comparative Study of Indonesia's Education System Strategy with Malaysia through an Institutional Approach - Al-Ayyub, Achmad Aqwa; Sirait, Anabelle Graciani Nathaniel; Putra, Azka Dwi; Razak, Sulthon; Yuningsih, Neneng Yani (Peneliti.net, 2025)
This article analyses the comparison of the education systems in Malaysia and Indonesia through an institutional approach, examining the theory and implementation of education in both countries. The study uses a library research approach with a descriptive qualitative methodology to interpret legal documents and educational policies from each country. The results of the comparison show that Indonesia has adopted a combination of centralised and decentralised systems, with centralised policies and relatively autonomous local implementation. Indonesia has implemented the Merdeka Curriculum, which focuses on developing character, creativity, and competencies through project-based learning, although it still faces challenges such as a shortage of teachers and disparities in teacher welfare. Conversely, Malaysia has implemented decentralisation, giving regions a relatively high degree of autonomy while maintaining coordination with the central government, with a curriculum that emphasises holistic individual development (JERIS) and is relatively stable. The Malaysian government also pays close attention to teacher well-being and learning innovation, supported by substantial education funding. In terms of curriculum development, the principles of Ralph Tyler's model, which include setting goals, selecting learning experiences, organising them, and evaluating them, are implemented in the education systems of both countries. This comparison highlights the need for policies to be adapted to the local context, as well as the importance of government support in terms of funding and teacher welfare to achieve national education goals comprehensively.